HALAL AWARE LITERACY AND HALAL CERTIFICATION ASSISTANCE WITH BUSINESS DECLARATION SCHEME (SELF DECLARE) FOR SMALL AND MICRO BUSINESSES IN TANGERANG DISTRICT, BANTEN - Zuhdi, Muhammad Luthfi; Aminah, Shobichatul; Qiwamudin, Qiwamudin (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Government policies related to the acceleration of halal certification for 10 million SMEs in 2024 will work well only if business actors, especially small and micro enterprises (SMEs), understand the importance of halal certification for their products, understand the procedures for applying for halal certificates, and business actors comply requirements in registering its products for halal certification. In fact, the importance of halal certification has not become knowledge that can be accepted by business actors. In addition, the halal certification procedure has not been well socialized among micro and small business actors. For this reason, community service related to halal awareness literacy and the dissemination of halal certification by the self-declare scheme of business actors among small and micro business actors is very important to do. The service team from the School of Strategic and Global UI Studies and the UI Halal Center have carried out community service with halal-aware literacy activities, socialization of submitting halal certificates through the siHalal application and assistance in the process of halal products as a procedure for submitting halal certificates for small and micro business actors in Tangerang Banten district